Cover Image, Volume 29, Issue 7. (15th June 2016) - Li, Wei; Long, Justin Alexander; Watts, Lora; Shen, Qiang; Liu, Yichu; Jiang, Zhao; Duong, Timothy Q.
Abstract : The cover image, by Timothy Q Duong et al., is based on the Research Article Spatiotemporal changes in diffusion, T2 and susceptibility of white matter following mild traumatic brain injury, DOI:10.1002/nbm.3536 .